Analysis and comprehension of childhood notion, its historical references and its influence in preschool development in Colombia - Merchán, Yamile Azucena Medina Villabona, Adriana Patricia Becerra Manosalva, Blanca Iris Rincón (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article deals with the genesis and consolidation of early childhood education or preschool in Colombia, from its source in the pedagogical model of the nineteenth-century France to its enactment as law degree mandatory or Act 115 of 1994 Colombian general education. During this historical review is an analysis of the emergence of the notion of childhood, its evolution, current status and future projections, from three basic considerations such as: The current preschool curriculum model, vision and expectations. This approach to childhood as an important stage in the formation of man, recognized the infant from many factors such as mindset, their families and training among others, which are assessed and analyzed to the fore the initial training as a means of generating the child's understanding of the environment where he lives and building tools to interact socially in all human sense.